Preparation method of silicon-carbon negative electrode slurry, silicon-carbon negative electrode slurry and lithium ion battery

By preparing a multi-stage synergistic effect containing silicon-carbon negative electrode slurry, the powdering and shedding of silicon-based negative electrode materials in lithium-ion batteries is solved, and the circulation performance and safety of the battery are improved.

CN120565580APending Publication Date: 2025-08-29JIANGXI FAR EAST LITHIUM BATTERY CO LTD

Patent Information

Application Number
CN202510700164.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing silicon-based negative electrode materials have the material powder and fall off due to volume expansion in lithium-ion batteries, reducing the cell cycle life and increasing safety risks. The existing modification methods have failed to effectively solve the problems of electrode sheet crisps and material drops.

Method used

The components of silicon-carbon negative electrode slurry include silicon-based materials, graphite materials, carbon black conductive agents, single-wall carbon nanotube conductive paste, carboxymethylcellulose sodium binder, polyacrylic binder, styrene butadiene rubber binder and N-methylpyrrolidone, and the conductive, bonding and dispersing properties of multi-stage synergistic effects are formed through specific stirring and dispersing steps, and a flexible network is built to buffer volume changing stress.

Benefits of technology

It significantly improves the stability of silicon-carbon negative electrode slurry and the circulation performance of lithium-ion batteries, extends the cycle life of the battery cell, improves the yield rate of the coating process, and reduces the risk of pole cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565580A_ABST
    Figure CN120565580A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a preparation method of silicon-carbon negative electrode slurry, the silicon-carbon negative electrode slurry and a lithium ion battery. The silicon-carbon negative electrode slurry comprises the following components: a silicon-based material, a graphite material, a carbon black conductive agent, a single-walled carbon nanotube conductive slurry, a sodium carboxymethyl cellulose binder, a polyacrylic acid binder, a styrene butadiene rubber binder, N-methyl pyrrolidone and deionized water. The silicon-carbon negative electrode slurry is prepared by adopting a dry process and a method of adding the binder step by step, so that the uniformity of the silicon-carbon negative electrode slurry is ensured, the expansion of the silicon-carbon negative electrode material is inhibited, and the cycle performance of the prepared lithium ion battery is finally improved. The silicon-based negative electrode paste has the following beneficial effects that the prepared silicon-based negative electrode paste is good in stability, and the single-walled carbon nanotube conductive paste, the sodium carboxymethyl cellulose binder, the polyacrylic acid binder and the styrene butadiene rubber binder form a multi-stage synergistic effect through complementary conductive, binding, dispersing and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a silicon-carbon negative electrode slurry, the silicon-carbon negative electrode slurry, and a lithium-ion battery. Background Art

[0002] Driven by the anxiety about the battery life of “faster and stronger” lithium-ion batteries and the demand for fast charging, the new energy market has an increasingly urgent demand for high-efficiency, high-energy-density lithium-ion batteries. From the perspective of negative electrode materials, given that the current commercial graphite gram capacity (360mAh / g) is close to its theoretical gram capacity upper limit (372mAh / g), continuing to increase the commercial graphite gram capacity can no longer meet market demand. There is an urgent need to find other negative electrode materials with high gram capacity. Among them, silicon materials stand out from the crowd of negative electrode materials with their gram capacity of up to 4200mAh / g. At the same time, silicon reserves are abundant and the price is moderate, making it a hot topic in the current research of lithium-ion battery negative electrode materials, with great research and application prospects. However, silicon materials undergo extremely severe volume expansion during the lithium insertion / delithiation process. The volume change of silicon materials in this process can reach more than 300%, causing severe cracking and pulverization of silicon particles in silicon-based materials, which makes the active material easily fall off from the current collector and ultimately leads to the attenuation of battery cell capacity and the decline of cycle performance.

[0003] To address the aforementioned issues of silicon-based material expansion and failure, the industry uses silicon-based negative electrode modification methods, including silicon oxidation, nano-sizing, composite, porosification, alloying, and pre-lithiation, in the silicon-based material production process to mitigate the volume expansion of silicon particles during the charge and discharge process. Composite, silicon oxidation, nano-sizing, and pre-lithiation technologies are relatively mature and have begun to be applied in industrialization. On the application side, a method for preparing a silicon-carbon negative electrode slurry is used, as shown in the Chinese invention patent with the published patent number CN114628648A. This technology alleviates the volume effect problem of silicon materials and suppresses negative electrode expansion by adding porous carbon with a highly developed specific surface area and pore structure. However, the electrode sheets prepared therefrom continuously expand and contract with the silicon-based material, and the stress on the electrode sheets increases continuously. In addition, the electrode sheets have insufficient viscoelasticity, which makes the negative electrode sheets prone to brittleness and material shedding, reducing the cycle life of the battery cell while increasing its safety risks. Summary of the Invention

[0004] The present invention provides a method for preparing a silicon-carbon negative electrode slurry, which aims to solve the problems of poor conductivity of silicon-based materials and material pulverization and shedding caused by volume expansion during charging and discharging, as well as increased stress, while ensuring the high capacity of the battery cell and extending the cycle life of the battery cell.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0006] In the first aspect, the present invention provides a silicon-carbon negative electrode slurry, whose components include silicon-based materials, graphite materials, carbon black conductive agents, single-walled carbon nanotube conductive slurry, sodium carboxymethyl cellulose binder, polyacrylic acid binder, styrene-butadiene rubber binder, N-methylpyrrolidone and deionized water.

[0007] In a second aspect, the present invention provides a method for preparing a silicon-carbon negative electrode slurry, comprising the following steps:

[0008] (1) stirring and dispersing the silicon-based material, the graphite material, and the carbon black conductive agent to uniformly mix the materials to obtain a mixed dry material A;

[0009] (2) adding the single-walled carbon nanotube conductive slurry and a certain amount of deionized water to the above-mentioned mixed dry material A, stirring and dispersing at a low speed, and scraping the material during stirring to obtain a wet mixed material B;

[0010] (3) adding sodium carboxymethyl cellulose binder to the wet mixture B, stirring and dispersing at a low speed, and scraping the mixture during stirring to obtain a wet mixture C;

[0011] (4) adding a polyacrylic acid binder and a certain amount of deionized water to the wet mixture C, stirring and dispersing the mixture, and controlling the viscosity of the slurry by adjusting the amount of deionized water added to obtain a suspended mixed slurry D;

[0012] (5) adding styrene-butadiene rubber binder and N-methylpyrrolidone to the above-mentioned suspended mixed slurry D, stirring and dispersing at a low speed in a vacuum environment to obtain a suspended mixed slurry E;

[0013] (6) The suspended mixed slurry E is subjected to vacuum defoaming treatment, and a silicon-carbon negative electrode slurry is obtained after stirring and sieving; the silicon-carbon negative electrode slurry is applied to a high-capacity and long-cycle-life lithium-ion battery through subsequent coating, rolling, slitting, liquid injection, and volume fractionation processes.

[0014] In the above-mentioned method for preparing a silicon-carbon negative electrode slurry, the stirring rate in step (1) is 15-25 rpm, the dispersion rate is 90-110 rpm, and the time is 20-30 min.

[0015] Preferably, in step (2), the stirring rate is 30-40 rpm, the dispersion rate is 350-450 rpm, and the time is 40-50 min.

[0016] Preferably, in step (3), the stirring rate is 25-35 rpm, the dispersion rate is 250-350 rpm, and the time is 80-100 min.

[0017] Preferably, in step (4), the stirring rate is 35-45 rpm, the dispersion rate is 1500-2000 rpm, and the time is 2-3 h.

[0018] Preferably, in step (5), the stirring rate is 20-30 rpm, the dispersion rate is 700-900 rpm, and the time is 25-35 min.

[0019] Preferably, in the step (1), the amounts of the materials used are as follows: 0 to 30 parts of silicon-based material, 65 to 95 parts of graphite material, and 0.4 to 0.6 parts of carbon black conductive agent, calculated by weight.

[0020] Preferably, the amount of single-walled carbon nanotube conductive paste added in step (2) is 0.2 to 0.3 parts.

[0021] Preferably, the amount of sodium carboxymethyl cellulose added in step (3) is 0.4 to 0.75 parts.

[0022] Preferably, the amount of the polyacrylic acid binder added in step (4) is 2.0 to 3.0 parts.

[0023] Preferably, in step (5), the amount of styrene-butadiene rubber binder added is 1.0 to 1.5 parts, and the amount of N-methylpyrrolidone added is 0 to 1 part.

[0024] Preferably, the silicon-based material in step (1) is at least one of a silicon-oxygen material and a silicon-carbon material.

[0025] Preferably, the graphite material in step (1) is at least one of artificial graphite and composite graphite.

[0026] Preferably, the stirring interval in step (2) is 0 to 5 minutes, and the number of scraping times is 0 to 2 times.

[0027] Preferably, the stirring interval in step (3) is 0 to 5 minutes, and the number of scraping times is 0 to 2 times.

[0028] Beneficial technical effects: In this application, silicon-based materials, graphite materials and carbon black conductive agents are mixed, and then single-walled carbon nanotube conductive slurry and sodium carboxymethyl cellulose are added step by step, and the material is scraped intermittently during stirring to ensure that the components of the wet mixture C are fully mixed and evenly dispersed, ensuring that the suspended mixed slurry E has excellent stability, which is conducive to the stable progress of the subsequent coating process, the production of silicon-carbon negative electrode sheets with good appearance and thickness distribution, and ultimately the improvement of the cycle performance of lithium-ion batteries.

[0029] Preferably, the amount of deionized water quantitatively added in step (2) is calculated based on the ratio of the theoretical designed solid content of the silicon-carbon negative electrode slurry and the theoretical total amount of deionized water required, and the ratio of the amount of deionized water added in step (2) is 35% to 45% of the theoretical total amount of deionized water required.

[0030] The theoretical design solid content and the theoretical specific calculation method are as follows:

[0031] Taking into account the solid content of other aqueous slurry materials such as single-walled carbon nanotube conductive paste, polyacrylic acid binder and styrene-butadiene rubber binder, their solid content values ​​can be obtained according to the manufacturer's material specifications, for example, 1%, 15% and 40% respectively; combined with the required input weight of each material in the design experiment table (unit: g, the same below): graphite W1, silicon-based material W2, conductive agent W3, single-walled carbon nanotube conductive paste W4, sodium carboxymethyl cellulose W5, polyacrylic acid binder and styrene-butadiene rubber binder W6 and W7 respectively, when the theoretical design solid content is X (0.46≤X≤0.5), the theoretical total amount of deionized water T required is calculated based on the input amount of different components. The specific calculation method is as follows:

[0032] 1) First calculate the total solid matter weight W0 of the silicon-based negative electrode slurry:

[0033] W0=W1+W2+W3+W5+W4*1%+W6*15%+W7*40%

[0034] 2) Calculate the total weight W of silicon-based negative electrode slurry:

[0035] W=W0 / X

[0036] 3) Calculate the theoretical total amount of deionized water T required:

[0037] T=W-W0.

[0038] Preferably, the amount of deionized water quantitatively added in step (4) is calculated based on the ratio of the theoretical designed solid content of the silicon-carbon negative electrode slurry and the theoretical total amount of deionized water required, and the ratio of the amount of deionized water added in step (4) is 55% to 65% of the theoretical total amount of deionized water required.

[0039] Preferably, the suspended mixed slurry D obtained in step (4) has a solid content of 46-50% and a viscosity in the range of 3000-5000 mPa·s.

[0040] Preferably, the viscosity of the suspended mixed slurry E obtained in step (5) is in the range of 3500 to 5500 mPa·s.

[0041] Preferably, in step (6), the stirring rate is 20-30 rpm, the dispersion rate is 350-450 rpm, the time is 20-30 min, and the mesh size of the discharge screen is 100-150 meshes.

[0042] In a third aspect, the present invention provides a high-capacity, long-cycle-life lithium-ion battery prepared by coating, rolling, slitting, winding, shelling, baking, liquid injection, and chemical composition with the above-mentioned silicon-carbon negative electrode slurry.

[0043] In a fourth aspect, the present invention provides that the high-capacity and long-cycle-life lithium-ion battery is a 18650-4000mAh cylindrical lithium-ion battery.

[0044] The present invention provides a silicon-carbon anode slurry, its preparation method, and its application. By leveraging the complementary conductivity, bonding, dispersion, and mechanical properties of single-walled carbon nanotube conductive slurry, sodium carboxymethyl cellulose binder, polyacrylic acid binder, and styrene-butadiene rubber binder, a multi-level synergistic effect is achieved. This effectively mitigates the problems of silicon-based anode materials, such as the poor conductivity of silicon in the silicon-carbon material and the pulverization of silicon-based anode materials caused by the large volume expansion of silicon during charge and discharge. This ensures high cell capacity while extending the cycle life of the cell. Experimental results demonstrate that the stability of the silicon-carbon anode slurry prepared using the present invention, as well as the capacity and cycle performance of the cell prepared using the present invention, are significantly improved.

[0045] Compared with the prior art, the present invention has the following beneficial technical effects:

[0046] 1. In this application, after mixing the silicon-based material, graphite material and carbon black conductive agent, the single-walled carbon nanotube conductive slurry and sodium carboxymethyl cellulose are added step by step, and the mixture is stirred and scraped intermittently to ensure that the components of the wet mixture C are fully mixed and evenly dispersed;

[0047] 2. This application forms a multi-level synergistic effect through the complementary conductivity, bonding, dispersion and mechanical properties of single-walled carbon nanotube conductive paste, sodium carboxymethyl cellulose binder, polyacrylic acid binder and styrene-butadiene rubber binder, effectively solving the problems of large volume effect and poor conductivity of silicon materials. On the one hand, the sodium carboxymethyl cellulose binder evenly disperses the single-walled carbon nanotubes and stabilizes the silicon-based negative electrode slurry. At the same time, the single-walled carbon nanotubes are combined with the flexible network formed by the polyacrylic acid binder and the styrene-butadiene rubber binder to construct a 3D conductive network, ensuring that it can maintain structural integrity and conductivity under the high strain conditions caused by the expansion and contraction of the silicon material. On the other hand, the single-walled carbon nanotubes have high mechanical strength, and the sodium carboxymethyl cellulose binder can stabilize the single-walled carbon nanotubes and the silicon particles in the silicon-carbon material while fixing the active material and the conductive agent. The polyacrylic acid binder provides strong bonding through the hydrogen bonds formed by its terminal carboxyl groups with the silicon material. Styrene-butadiene rubber, as an elastic binder, can absorb the mechanical stress generated by the silicon material during the expansion / contraction process by forming a flexible network after coating and drying. The superposition of the above characteristics gives the silicon-carbon negative electrode slurry described in this application a "rigid and flexible" bonding system. The silicon-carbon negative electrode sheet prepared in this way can effectively buffer the volume change stress generated by the silicon material during the expansion / contraction process, reduce electrode cracks and prevent the active material from falling off, which is beneficial to the improvement of the cycle performance of the lithium-ion battery.

[0048] 3. In the preparation process of the silicon-carbon negative electrode slurry, the present application utilizes the dispersing effect of the sodium carboxymethyl cellulose binder, combined with the bonding properties of the polyacrylic acid binder and the styrene-butadiene rubber binder, to ensure the uniformity and stability of the suspended mixed slurry E. Furthermore, the addition of N-methyl pyrrolidone can prevent the negative electrode from cracking during coating. This effectively avoids the cracking problem that may occur during drying of the electrode during the coating process of the silicon-carbon negative electrode slurry, thereby improving the yield rate of the coating process.

[0049] 4. The present application can enhance the interfacial bonding with the silicon material through the polar carboxyl group at the end of the polyacrylic acid binder; if the silicon-based material is selected from CVD silicon-carbon material, a small amount of oxygen-containing groups such as carboxyl and hydroxyl groups in the carbon layer on the surface of the CVD silicon-carbon material can form an indirect connection of "carbon-polyacrylic acid binder-silicon" with the polyacrylic acid binder through hydrogen bonds or electrostatic effects. At the same time, the polyacrylic acid binder and the carbon layer of the CVD silicon-carbon material can also form a dense polymer network, reduce the shedding of silicon particles, stabilize the SEI film formed in the subsequent chemical composition process, and cooperate with the carbon coating layer as a physical barrier to effectively inhibit the side reactions between the silicon material and the electrolyte, thereby improving the cycle life of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1This is a cycle performance diagram of a high-capacity, long-cycle-life 18650-4000mAh cylindrical lithium-ion battery prepared in the comparative example and embodiment of the present invention through subsequent coating, rolling, slitting, liquid injection, and volume fractionation processes. DETAILED DESCRIPTION

[0051] In order to make the technical solutions of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below through the examples of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention. In fact, it should be clear to those skilled in the art that any modifications and / or changes made to the present invention without departing from the scope or spirit of the present invention will fall within the scope of protection of the present invention.

[0052] In the present invention, unless otherwise specified, all parts and percentages are by weight, and all equipment and raw materials can be purchased from the market or are commonly used in the industry.

[0053] Example 1

[0054] Prepare silicon-carbon negative electrode slurry components including 22 parts of CVD silicon-carbon material, 73 parts of artificial graphite material, 0.5 parts of carbon black conductive agent, 0.25 parts of single-walled carbon nanotube conductive slurry, 0.75 parts of sodium carboxymethyl cellulose binder, 2.5 parts of polyacrylic acid binder, 1.0 parts of styrene-butadiene rubber binder, 1.0 parts of N-methylpyrrolidone and deionized water, and set the solid content to 0.5; the solid content value of the material selected for 0.25 parts of single-walled carbon nanotube conductive slurry is 1%; the solid content value of the material selected for 2.5 parts of polyacrylic acid binder is 15%; the solid content value of the material selected for 1.0 parts of styrene-butadiene rubber binder is 40%; theoretically, the total amount of deionized water prepared is: 97.0275 parts.

[0055] The preparation method of the silicon-carbon negative electrode slurry comprises the following steps:

[0056] (1) 22 parts of CVD silicon-carbon material, 73 parts of artificial graphite material and 0.5 parts of carbon black conductive agent were mixed at a stirring rate of 20 rpm and a dispersion rate of 100 rpm for 30 minutes to obtain a mixed dry material A;

[0057] (2) adding 0.25 parts of single-walled carbon nanotube conductive paste and 40% of the total amount of deionized water theoretically required to be added to the above-mentioned mixed dry material A, stirring at a speed of 35 rpm and a dispersion speed of 400 rpm for 45 minutes, and scraping twice with stirring intervals of 5 minutes every 20 minutes to obtain a wet mixed material B;

[0058] (3) adding 0.75 parts of sodium carboxymethyl cellulose binder to the wet mixture B, mixing the materials for 90 minutes at a stirring rate of 30 rpm and a dispersion rate of 300 rpm, and scraping the materials twice with a stirring interval of 5 minutes every 30 minutes to obtain a wet mixture C;

[0059] (4) adding 2.5 parts of a polyacrylic acid binder and deionized water accounting for 50% of the total amount of deionized water theoretically required to the wet mixed material C, mixing the materials for 2.5 hours at a stirring rate of 40 rpm and a dispersion rate of 1800 rpm, and controlling the slurry viscosity by adjusting the amount of deionized water added accounting for 10% of the total amount of deionized water theoretically required to obtain a suspended mixed slurry D having a solid content of 46-50% and a viscosity range of 3000-5000 mPa·s;

[0060] (5) adding 1.0 part of styrene-butadiene rubber binder and 1.0 part of N-methylpyrrolidone to the above-mentioned suspended mixed slurry D, and mixing the above materials for 30 minutes under a vacuum environment at a stirring rate of 30 rpm and a dispersion rate of 800 rpm to obtain a suspended mixed slurry E having a viscosity ranging from 3500 to 5500 mPa·s;

[0061] (6) The suspended mixed slurry E was subjected to vacuum degassing treatment, stirred at a stirring rate of 30 rpm, a dispersion rate of 400 rpm, and a stirring time of 20 minutes, and then sieved with a 150-mesh sieve to obtain a silicon-carbon negative electrode slurry. The silicon-carbon negative electrode slurry was subsequently applied to 18650-4000 mAh cylindrical lithium-ion batteries with high capacity and long cycle life through subsequent processes such as coating, rolling, slitting, liquid injection, and volume fractionation.

[0062] Example 2

[0063] Prepare silicon-carbon negative electrode slurry components including 22 parts of CVD silicon-carbon material, 73 parts of artificial graphite material, 0.5 parts of carbon black conductive agent, 0.25 parts of single-walled carbon nanotube conductive slurry, 0.75 parts of sodium carboxymethyl cellulose binder, 2.5 parts of polyacrylic acid binder, 1.0 parts of styrene-butadiene rubber binder, 1.0 parts of N-methylpyrrolidone and deionized water, and set the solid content to 0.5; the solid content value of the material selected for 0.25 parts of single-walled carbon nanotube conductive slurry is 1%; the solid content value of the material selected for 2.5 parts of polyacrylic acid binder is 15%; the solid content value of the material selected for 1.0 parts of styrene-butadiene rubber binder is 40%; theoretically, the total amount of deionized water prepared is: 97.0275 parts.

[0064] The preparation method of the silicon-carbon negative electrode slurry comprises the following steps:

[0065] (1) 22 parts of CVD silicon-carbon material, 73 parts of artificial graphite material and 0.5 parts of carbon black conductive agent were mixed at a stirring rate of 20 rpm and a dispersion rate of 100 rpm for 30 minutes to obtain a mixed dry material A;

[0066] (2) adding 0.25 parts of single-walled carbon nanotube conductive paste and 40% of the total amount of deionized water theoretically required to the mixed dry material A, and mixing the above materials for 45 minutes at a stirring rate of 35 rpm and a dispersion rate of 400 rpm to obtain a wet mixed material B;

[0067] (3) adding 0.75 parts of sodium carboxymethyl cellulose binder to the wet mixture B, and mixing the materials for 90 minutes at a stirring rate of 30 rpm and a dispersion rate of 300 rpm to obtain a wet mixture C;

[0068] (4) adding 2.5 parts of a polyacrylic acid binder and deionized water accounting for 50% of the total amount of deionized water theoretically required to the wet mixed material C, mixing the materials for 2.5 hours at a stirring rate of 40 rpm and a dispersion rate of 1800 rpm, and controlling the slurry viscosity by adjusting the amount of deionized water added accounting for 10% of the total amount of deionized water theoretically required to obtain a suspended mixed slurry D having a solid content of 46-50% and a viscosity range of 3000-5000 mPa·s;

[0069] (5) adding 1.0 part of styrene-butadiene rubber binder and 1.0 part of N-methylpyrrolidone to the above-mentioned suspended mixed slurry D, and mixing the above materials for 30 minutes under a vacuum environment at a stirring rate of 30 rpm and a dispersion rate of 800 rpm to obtain a suspended mixed slurry E having a viscosity ranging from 3500 to 5500 mPa·s;

[0070] (6) The suspended mixed slurry E was subjected to vacuum degassing treatment, stirred at a stirring rate of 30 rpm, a dispersion rate of 400 rpm, and a stirring time of 20 minutes, and then sieved with a 150-mesh sieve to obtain a silicon-carbon negative electrode slurry. The silicon-carbon negative electrode slurry was subsequently applied to 18650-4000 mAh cylindrical lithium-ion batteries with high capacity and long cycle life through subsequent processes such as coating, rolling, slitting, liquid injection, and volume fractionation.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that the silicon-based material used in step (1) is a pre-lithium silicon-oxygen material.

[0073] Comparative Example 2

[0074] The difference from Example 1 is that the silicon-based material used in step (1) is a ball-milled silicon-carbon material, and the stirring intermittent scraping process is not performed in steps (2) and (3).

[0075] Test results

[0076] The silicon-based negative electrode slurries obtained in Examples 1-2 and Comparative Examples 1-2 were coated to obtain silicon-based negative electrode sheets. These sheets were then applied to high-capacity, long-cycle-life 18650-4000mAh cylindrical lithium-ion batteries through processes such as coating, rolling, slitting, injection, and volume fractionation. The silicon-based negative electrode sheet peeling force test and the 18650-4000mAh cylindrical lithium-ion battery cycle performance test were then performed. The specific test conditions were:

[0077] Width: The silicon-based negative electrode sheet was cut into 20 mm wide and 200 mm long sheets using a cutting machine, and the peeling force test was performed using a micro-controlled electronic universal testing machine.

[0078] Cycle test: At 25℃, 0.5C charge and 1C discharge, voltage range 2.75-4.2V.

[0079] Table 1: Comparative performance of negative electrode sheet peeling force of examples and comparative examples (unit: N)

[0080] Group average value Test value 1 Test value 2 Test value 3 Test value 4 Test value 5 Example 1 0.4972 0.5576 0.4627 0.4967 0.4978 0.4711 Example 2 0.4878 0.4711 0.5192 0.4935 0.4807 0.4743 Comparative Example 1 0.2898 0.2525 0.2424 0.3497 0.2971 0.3075 Comparative Example 2 0.2353 0.2307 0.2323 0.2173 0.2452 0.2511

[0081] From Table 1 and Figure 1 The data shows that the mechanical properties and cycle performance of the silicon-based negative electrode sheets obtained in Examples 1 and 2 are significantly better than those in Comparative Examples 1 and 2, indicating that the lithium-ion batteries prepared in this embodiment have excellent overall performance. The reason for this is that, firstly, stirring and intermittent scraping during the preparation of the silicon-based negative electrode slurry can ensure that the components of the silicon-carbon negative electrode slurry are fully mixed and evenly dispersed. Secondly, the complementary conductivity, bonding, dispersion, and mechanical properties of the single-walled carbon nanotube conductive slurry, sodium carboxymethyl cellulose binder, polyacrylic acid binder, and styrene-butadiene rubber binder can form a multi-level synergistic effect, effectively alleviating the problems of the silicon-based negative electrode material being easily pulverized due to the poor conductivity of the silicon material in the silicon-carbon material and the large volume expansion of the silicon material during charge and discharge, thereby ensuring the high capacity of the battery cell while extending the cycle life of the battery cell.

[0082] At the same time, by comparing the mechanical properties and cycle performance of the silicon-based negative electrode obtained by Example 1 and Comparative Example 1, the former is significantly better than the latter. Analysis shows that: compared with the pre-lithium silicon-oxygen material, the polyacrylic acid binder and the carbon layer of the CVD silicon-carbon material can form a dense polymer network, reduce the shedding of silicon particles, stabilize the SEI film formed in the subsequent composition process, and can cooperate with the carbon coating layer as a physical barrier to effectively inhibit the side reactions between the silicon material and the electrolyte, thereby improving the cycle life of the battery cell.

Claims

1. A method for preparing a silicon-carbon negative electrode slurry, characterized in that: The silicon-carbon negative electrode slurry components include silicon-based materials, graphite materials, carbon black conductive agents, single-walled carbon nanotube conductive slurry, sodium carboxymethyl cellulose binder, polyacrylic acid binder, styrene-butadiene rubber binder, N-methyl pyrrolidone and deionized water; the preparation method of the silicon-carbon negative electrode slurry includes the following steps: (1) stirring and dispersing the silicon-based material, the graphite material, and the carbon black conductive agent, and uniformly mixing the materials to obtain a mixed dry material A; (2) adding the single-walled carbon nanotube conductive slurry and a certain amount of deionized water to the above-mentioned mixed dry material A, stirring and dispersing at a low speed, and scraping the material during stirring to obtain a wet mixed material B; (3) adding sodium carboxymethyl cellulose binder to the wet mixture B, stirring and dispersing at a low speed, and scraping the mixture during stirring to obtain a wet mixture C; (4) adding a polyacrylic acid binder and a certain amount of deionized water to the wet mixture C, stirring and dispersing the mixture, and controlling the viscosity of the slurry by adjusting the amount of deionized water added to obtain a suspended mixed slurry D; (5) adding styrene-butadiene rubber binder and N-methylpyrrolidone to the above-mentioned suspended mixed slurry D, stirring and dispersing at a low speed in a vacuum environment to obtain a suspended mixed slurry E; (6) The suspended mixed slurry E is subjected to vacuum defoaming treatment, and a silicon-carbon negative electrode slurry is obtained after stirring and sieving.

2. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, characterized in that: In the step (1), the stirring rate is 15-25 rpm, the dispersion rate is 90-110 rpm, and the time is 20-30 min; in the step (2), the stirring rate is 30-40 rpm, the dispersion rate is 350-450 rpm, and the time is 40-50 min; in the step (3), the stirring rate is 25-35 rpm, the dispersion rate is 250-350 rpm, and the time is 80-100 min; in the step (4), the stirring rate is 35-45 rpm, the dispersion rate is 1500-2000 rpm, and the time is 2-3 h; in the step (5), the stirring rate is 20-30 rpm, the dispersion rate is 700-900 rpm, and the time is 25-35 min.

3. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, characterized in that: In the step (1), the amounts of the materials used are as follows: 0 to 30 parts by weight of silicon-based material, 65 to 95 parts by weight of graphite material, and 0.4 to 0.6 parts by weight of carbon black conductive agent; in the step (2), the amount of single-walled carbon nanotube conductive paste added is 0.2 to 0.3 parts; in the step (3), the amount of sodium carboxymethyl cellulose added is 0.4 to 0.75 parts; in the step (4), the amount of polyacrylic acid binder added is 2.0 to 3.0 parts; in the step (5), the amount of styrene-butadiene rubber binder added is 1.0 to 1.5 parts, and the amount of N-methyl pyrrolidone added is 0 to 1 part.

4. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, wherein: In the step (1), the silicon-based material is at least one of a silicon-oxygen material and a silicon-carbon material, and the graphite material is at least one of an artificial graphite and a composite graphite.

5. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, characterized in that: The stirring interval time in step (2) and step (3) is 0 to 5 minutes, and the scraping times is 0 to 2 times.

6. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, wherein: The amount of deionized water quantitatively added in step (2) and step (4) is calculated based on the theoretical design solid content of the silicon-carbon negative electrode slurry according to claim 1 and the theoretical total amount of deionized water required. The ratio of the amount of deionized water added in step (2) is 35% to 45% of the theoretical total amount of deionized water required, and the ratio of the amount of deionized water added in step (4) is 55% to 65% of the theoretical total amount of deionized water required.

7. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, characterized in that: The solid content of the suspended mixed slurry D obtained in step (4) is 46-50%, and the viscosity range is 3000-5000 mPa·s; the viscosity range of the suspended mixed slurry E obtained in step (5) is 3500-5500 mPa·s.

8. The method for preparing a silicon-carbon negative electrode slurry according to claim 1, wherein: In the step (6), the stirring rate is 20-30 rpm, the dispersion rate is 350-450 rpm, the time is 20-30 min, and the mesh number of the discharge screen is 100-150 meshes.

9. Silicon-carbon negative electrode slurry, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. A lithium-ion battery, characterized in that A high-capacity, long-cycle-life lithium-ion battery prepared by coating, rolling, slitting, winding, shelling, baking, liquid injection, and chemical composition with the silicon-carbon negative electrode slurry according to claim 9; the lithium-ion battery is a high-capacity, long-cycle-life lithium-ion battery; the high-capacity, long-cycle-life lithium-ion battery is an 18650-4000mAh cylindrical battery.

Citation Information

Patent Citations

  • High-performance silicon-carbon negative electrode plate and preparation method thereof

    CN114628648A

Cited By

  • Negative electrode material, negative electrode slurry, preparation method of negative electrode slurry, negative electrode plate, secondary battery and electric device

    CN121237859A

  • Homogenizing process of lithium ion battery silicon-carbon negative electrode slurry and negative electrode slurry

    CN121366876A